Cancer stem-like cells stay in a plastic state ready for tumor evolution - Jiali Xu; Houde Zhang; Zhihao Nie; Wenyou He; Yichao Zhao; Zhenhui Huang; Lin Jia; Zhiye Du; Baotong Zhang; Siyuan Xia (Neoplasia: An International Journal for Oncology Research)
Cell plasticity emerges as a novel cancer hallmark and is pivotal in driving tumor heterogeneity and adaptive resistance to different therapies. Cancer stem-like cells (CSCs) are considered the root of cancer. While first defined as tumor-initiating cells with the potential to develop a heterogeneous tumor, CSCs further demonstrate their roles in cancer metastasis and adaptive therapeutic resistance. Generally, CSCs come from the malignant transformation of somatic stem cells or the de-differentiation of other cancer cells. The resultant cells gain more plasticity and are ready to differentiate into different cell states, enabling them to adapt to therapies and metastatic ecosystems. Therefore, CSCs are likely the nature of tumor cells that gain cell plasticity. However, the phenotypic plasticity of CSCs has never been systematically discussed. Here, we review the distinct intrinsic signaling pathways and unique microenvironmental niches that endow CSC plasticity in solid tumors to adapt to stressful conditions, as well as emerging opportunities for CSC-targeted therapy.